"We Should Have Maintained This Unity, Then There Would Be More Development:" Lessons from a Pop-Up Museum of the Fante Confederation. (10th June 2019) - Getz, Trevor R.; Ehrisman, Lindsay; Yeboah, Tony
Abstract: This article examines the potential of an unconventional method in applied history – the pop-up museum – for analyzing relationships between history and memory and producing meaningful histories of African pasts. Specifically, we assess our application of this tool to accounts of events surrounding the Fante Confederation of 1868–1873 in the Central Region of modern-day Ghana. By utilizing a pop-up museum exhibit in the field, we determined that the construction of a meaningful history of the Fante Confederation requires the apperception of "durable bundles" – continuities between collective memory and history that also serve as survivals from the mid-nineteenth century to contemporary society. Our original sources and interlocutors in common identified themes of "unity" and "development" as particularly meaningful durable themes. We posit that these shared themes can serve as points of attachment for contemporary Fante speakers to work with histories of the Fante Confederation, and propose them as motifs around which relevant histories can be built in this case. Finally, in reflecting on our experience, we hypothesize that this model of applied history may be useful in other situations as well. Résumé: Cet article examine le potentiel d'une méthode non conventionnelle en histoire appliquée – le musée éphémère – pour analyser les relations entre histoire et mémoire et pour produire des histoires pertinentes du passé africain. Plus précisément, nous appliquons cet outil à des récits d'événements entourant la Confédération Fante (1868–1873) dans la région centrale du Ghana actuel. En utilisant une exposition d'un musée éphémère sur le terrain, nous avons déterminé que la construction d'une histoire significative de la Confédération Fante nécessite la compréhension de "faisceaux durables" – continuités entre la mémoire collective et l'histoire qui servent également de témoins historiques du milieu du XIXe siècle pour la société contemporaine. Nos sources originales et nos interlocuteurs communs ont identifié les thèmes d'"unité" et de "développement" comme des thèmes durables particulièrement pertinents. Nous suggérons que ces thèmes partagés peuvent servir de points de repère pour les locuteurs Fante actuels afin de travailler avec les histoires de la Confédération Fante. Ces thèmes peuvent aussi devenir des motifs autour desquels des histoires pertinentes peuvent être construites. Enfin, en réfléchissant à notre expérience, nous émettons l'hypothèse que ce modèle d'histoire appliquée peut aussi être utile dans d'autres situations.